2021
DOI: 10.1002/jmv.26721
|View full text |Cite
|
Sign up to set email alerts
|

Week 96 resistance analyses of the once‐daily, single‐tablet regimen (STR) darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) in adults living with HIV‐1 from the phase 3 randomized AMBER and EMERALD trials

Abstract: In AMBER and EMERALD, darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg demonstrated high virological response and low virological failure (VF) through week 96. Week 96 resistance analyses are presented. Post‐baseline samples for genotyping/phenotyping were analyzed from protocol‐defined‐VFs with viral load (VL) ≥ 400 copies/ml at failure/later time points. Post‐hoc analyses were deep sequencing (AMBER) and HIV‐1 proviral DNA sequencing from baseline samples (VL < 50 copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…As described previously, M184V was detected pretreatment at screening by deep sequencing as a minority variant (9%). 22 These results are consistent with previous DRV and D/C/F/TAF studies and the established high genetic barrier to resistance of DRV. 9,43,44 The lack of emergence of significant resistance mutations over time for virologically suppressed, treatment-experienced patients is important, particularly given concerns for re-emergence of archived RAMs in patients with prior VF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As described previously, M184V was detected pretreatment at screening by deep sequencing as a minority variant (9%). 22 These results are consistent with previous DRV and D/C/F/TAF studies and the established high genetic barrier to resistance of DRV. 9,43,44 The lack of emergence of significant resistance mutations over time for virologically suppressed, treatment-experienced patients is important, particularly given concerns for re-emergence of archived RAMs in patients with prior VF.…”
Section: Discussionsupporting
confidence: 92%
“…There was no exclusion based on other PI or N(t)RTI RAMs, including FTC or TFV RAMs. 14,22,31 As such, ART-experienced, virologically suppressed patients with varied treatment histories, including history of VF, were allowed to enroll, so the population was more treatment-experienced than in most reported clinical switch studies. 14,22,31 In AMBER and EMERALD, D/C/F/TAF maintained high sustained virologic response rates at Week 96 across patient subgroups, ranging from 70% to 89% in ART-naïve patients in AMBER and 86% to 94% in ART-experienced, virologically suppressed patients in EMERALD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data have shown that in addition to B/F/TAF, other three-drug regimens, such as DTG/ABC/3TC and cobicistat-boosted elvitegravir or darunavir with FTC/TAF also have high efficacy in virologically suppressed PWH with M184V/I who switch to these regimens [37,50–52]. Factors contributing to the efficacy of three-drug FTC or 3TC-containing regimens against M184V/I include third agents with high barriers to resistance, reduced replicative fitness and higher RT fidelity of HIV carrying M184V/I [10,53–56], and/or increased activity of tenofovir against M184V/I mutants [57,58].…”
Section: Discussionmentioning
confidence: 99%